The Long‐Term Consequences of Short‐Term Incentives - EDMANS, ALEX; FANG, VIVIAN W.; HUANG, ALLEN H. (Journal of Accounting Research, 2022)
ABSTRACT This paper studies the long‐term consequences of actions induced by vesting equity, a measure of short‐term incentives. Vesting equity is positively associated with the probability of a firm repurchasing shares, the amount of shares repurchased, and the probability of the firm announcing a merger and acquisition (M&A). However, it is also associated with more negative long‐term returns over two to three years following repurchases and four years following M&A, as well as future M&A goodwill impairment. These results are inconsistent with CEOs buying underpriced stock or companies to maximize long‐run shareholder value, but consistent with these actions being used to boost the short‐term stock price and thus equity sale proceeds. CEOs sell their own stock shortly after using company money to buy the firm's stock, also inconsistent with repurchases being motivated by undervaluation.